Visco-Da Rios Equation in 3-Dimensional Riemannian Manifold - Gürbüz, Nevin Ertuğ; Yoon, Dae Won (Frontiers in Physics, 2022)
In this paper, we study two classes of a space curve evolution in terms of Frenet frame for the visco-Da Rios equation in a 3-dimensional Riemannain manifold. Also, we obtain the connection between the visco-Da Rios equation and nonlinear Schrödinger equation for two classes in a 3-dimensional Riemannain manifold with constant sectional curvature. Finally, we give the B\"acklund transformations of space curve with the visco-Da Rios equation.